Investigation of Photoelectrochemical Performance under the Piezoelectric Effect Based on Different Zinc Oxide Morphologies - Dong Wang; Rui Liu; Changcun Han; Baohua Tan; Qian Fu; Zhifeng Liu (Inorganics, 2022)
Recently, the piezoelectric effect has been widely used in photoelectrochemical (PEC) water splitting, and the morphology of the piezoelectric material is a critical factor affecting the piezo-photoelectrochemical water splitting performance. Herein, we explored the mechanism of the piezo-photoelectrochemical performance of zinc oxide (ZnO) that is affected by the morphology. Firstly, three different ZnO nanostructures (nanosheets, nanorods, and nanospheres) were synthesized by the electrodeposition, hydrothermal, and sol-gel methods, respectively. Then, the measurements of PEC water splitting performance under the piezoelectric effect revealed a 3-fold increase for the ZnO nanosheets, a 1.4-fold increase for the nanorods, and a 1.2-fold increase for the nanospheres compared to no piezoelectric effect. Finally, finite element simulation showed that nanosheets generated the highest piezoelectric potential (0.6 V), followed by nanorods (0.2 V), and nanospheres the lowest (0.04 V). Thus, among the three morphologies, the ZnO nanosheets exhibited a great improvement in PEC performance under the piezoelectric effect. The great improvement is due to the non-axial vertical homogeneous growth of the ZnO nanosheets, subjecting them to the highest effective deformation stress, which enables the ZnO nanosheets to produce the highest piezoelectric potential to accelerate the carrier separation and limit the recombination of photoelectrons and holes. This work serves as a guide for developing various photoelectrodes that are used in piezo-photoelectrochemical water splitting.